SYSTEM SOLUTIONS FOR THE DEVELOPMENT OF PROJECT MANAGEMENT AT THE ENTERPRISES OF THE DEFENSE INDUSTRY COMPLEX OF THE REPUBLIC OF KAZAKHSTAN - Tulembayev A.N.; Adilova A.M.; Shildibekov E. Zh.; Seidaliyeva D.; Serikbekuly A. (Academic Journal of Physical and Chemical Sciences, 2020)
This article is devoted to studying the features of ongoing projects at the enterprises of the militaryindustrial complex of Kazakhstan and identifying opportunities for the implementation of project management information systems (PMIS) in this industry.To achieve short-term and long-term goals, companies work on many logical tasks. The operational management process is an essential component of an enterprise management system. An increasing number of enterprises (if not all) of various fields of activity, identify project activity as an important and specific part of management. And the process of managing the activities of modern enterprises is increasingly based on the use of digital technologies. Current trends in the development of the military-industrial complex (MIC) determine the need to involve the potential of digital technologies, however, the lack of resources and mechanisms associated with system solutions for defense industry enterprises, require the involvement of existing and effectively functioning software products in this process. In this regard, the authors analyzed the essential project management software products, studied the implementation process of the project management information system, and described the implementation stages and possible problems that managers most often encounter when implementing the PMIS.